Solve by the addition method: 3x - 4y = 11 and -3x + 2y = -7 Check your solution.
3x=-4y+11
3x/3=(-4y+11)/3
x=(-4y+11)/3 Teacher: Sorry, I have no idea what you are doing here. There are two equations and this is a system. Therefore, they must be solved together.
Check: 3x - 4y = 11
3((-4y+11)/3)+4y=11
-4y+11+4y=11
-4y+4y+11=11
11=11
-3x + 2y = -7
(-3x)/(-3)=(-2y-7)/(-3)
3x/3=(2y+7)/3
x=(2y+7)/3
Check:-3x + 2y = -7
-3*((2y+7)/3)+2y=-7
-3*(2y+7)/3+2y=-7
-(2y+7)+2y=-7
-2y-7+2y=-7
-2y+2y=0
0=0
Teacher: Sorry wrong
2006-09-27
19:10:16
·
10 answers
·
asked by
SCHNITZEL
1
in
Science & Mathematics
➔ Mathematics
SOLUTION CHECK? This is the roblem
Teacher does not like myCheck:
2006-09-27
19:36:12 ·
update #1
3x - 4y = 11 - - - - - - - - - -Equation 1
-3x + 2y = - 7 - - - - - - - - -Equation 2
- 2y = 4
- 2y/- 2 = 4/- 2
y = - 2
The solution set is { - 2 }
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Solving for x for equation 1
3x - 4y = 11
3x - 4( -2 ) = 11
3x + 8 = 11
3x + 8 - 8 = 11 - 8
Subtracting - 8 from both sides of the equation
3x = 3
3x/3 = 3/3
Dividing both sides of the equation by 3
x = 1
The solution set is { 1 }
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Check for equation 1
3x - 4y = 11
3(1) - 4(-2) = 11
3 + 8 = 11
11 = 11
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
- 3x + 2y = - 7
- 3(1) +2(-2) = -7
- 3 + -4 = -7
- 3 - 4 = - 7
- 7 = - 7
- - - - - - - - - - - - - - - - - - - - - - - - - -
The answer is
x = 1
y = -2
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
The solution set
{ 1, -2 }
2006-09-28 03:33:14
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
3x - 4y = 11
-3x + 2y = -7 (add the two equations together)
-----------------
0 -2y = 4
y = -2
substitute y = -2 into equation 1
3x + (-4*-2) = 11
3x + 8 = 11
3x = 3
x = 1
Alternatively to solve for x
3x + 4y = 11
-3x + 2y = -7
This time you want the ys to cancel out so multiply equation 2 by 2
2(-3x+2y) = 2*-7
-6x + 4Y = -14 Put the equations back together and add:
3x + 4y = 11
-6x + 4Y = -14
-------------------
-3x = -3
x = 1
Check the solution (in equation 1 or 2)
3*1 + (-4*-2) = 11
3 + 8 = 11
11 = 11 correct
or
-3*1 + 2*-2 = -7
-3 -4 = -7
-7 = -7 correct
You beauty!
2006-09-27 20:24:01
·
answer #2
·
answered by uselessadvice 4
·
0⤊
0⤋
3x - 4y = 11 and -3x + 2y = -7
add both equations
3x - 4y +(-3x) + 2y = 11 +(-7)
3x -3x -4y +2y = 11 - 7
cancel both 3x
-4y +2y = 11 - 7
-2y = 4
y = -2
3x - 4(-2) = 11
3x +8 = 11
3x = 3
x = 1
check
3(1) - 4(-2) = 11 and -3(1) + 2(-2) = -7
3 + 8 = 11 and -3 - 4 = -7
11 = 11 and -7 = -7
fin
2006-09-27 21:39:11
·
answer #3
·
answered by Croasis 3
·
0⤊
0⤋
y=-2
you place the equations on top of each other, the negative 3x and positive 3x cancel each other out.
then you have
-4y=11 over
2y=-7
-2y=4
divide by -2
y=-2
two ways to solve for x, simply plug in -2 for y into either equation or....
too solve for x you must eliminate the y's the same way you first eliminated the x.
Multiply the second equation by 2, this will make the keep the first y as -4y and the second y as 4y, you can now cancel them out.
now you have -3x=-3
x=1
2006-09-27 19:12:30
·
answer #4
·
answered by gq1412@sbcglobal.net 3
·
0⤊
0⤋
3x - 4y = 11
-3x + 2y = -7
_______________
0*X-2y= 4
-2y=4
y=- 2
3x -4 (-2)=11
3x+8=11
3x=3
x=1
check: 3x - 4y = 11
-3x + 2y = -7
x=1, y=-2
3*1-4*(-2)=11
3+8=11
-3*(1)+2*(-2)=-7
-3-4=-7
-7=-7
2006-09-27 19:16:59
·
answer #5
·
answered by oana o 2
·
0⤊
0⤋
3x-4y=11____ eqn 1
-3x+2y=-7____ eqn 2
____________
-2y=4
______________
y=4/-2
=-2
substituting either in 1 or 2
from eqn 2
-3x+2y=-7
-3x+2(-2)=-7(substitute here y=-2)
-3x-4=-7
-3x=-7+4
-3x=-3
x=3/3=1(cancel minus sign on both sides)
x=1
the solution set is {1,-2}
check:
consider eqn 1
3x-4y=11
substitute x and y
left hand side 3(1)-4(-2)=3+8=11 that is right hand side
our solution is correct.
2006-09-27 22:38:14
·
answer #6
·
answered by srirad 2
·
0⤊
0⤋
you started off wrong, 3x = 4y+11 not -4y+11, try doing it with that changed.
2006-09-27 19:13:40
·
answer #7
·
answered by Will C 2
·
0⤊
0⤋
Something is missing in the instructions as to how to approach this problem. If you substitute 2 for y and run the equations one ends up as y=19/3 and the other y=11/3
I don't think so.............................
2006-09-27 19:28:28
·
answer #8
·
answered by Harley Charley 5
·
0⤊
0⤋
I'd tell your teacher to shove it. Cuz your not gonna use this crap when you get out of high school anyway. I'd tell him or her to shut up, and go back to addition and subtraction. It's much easier. Or, tell him or her to put the same letter. . i.e. . . 4x + 3x = 7x . .. . . thats much easier than 4x + 3y
2006-09-27 19:19:36
·
answer #9
·
answered by mulberry_hs_graduate_2002 2
·
0⤊
0⤋
3x - 4y = 11
-3x + 2y = -7
___________
0x - 2y = 4
___________
y = -2
-----------------
3x - 4 (-2) = 11
______________
3x + 8 = 11
________________
3x = 3
_______________
x = 1
therefore
x = 1, y = -2
2006-09-27 19:19:24
·
answer #10
·
answered by B T 3
·
0⤊
0⤋